Wormhole-induced ALP dark matter - Dhong Yeon Cheong; Koichi Hamaguchi; Yoshiki Kanazawa; Sung Mook Lee; Natsumi Nagata; Seong Chan Park (Journal of High Energy Physics)
Abstract Non-perturbative gravitational effects induce explicit global symmetry breaking terms within axion models. These exponentially suppressed terms in the potential give a mass contribution to the axion-like particles (ALPs). In this work we investigate this scenario with a scalar field charged under a global U(1) symmetry and having a non-minimal coupling to gravity. Given the exponential dependence, the ALP can retain a mass spanning a wide range, which can act as a dark matter component. We specify pre-inflationary and post-inflationary production mechanisms of these ALPs, with the former from the misalignment mechanism and the latter from both the misalignment and cosmic-string decay. We identify the allowed parameter ranges that explain the dark matter abundance for both a general inflation case and a case where the radial mode scalar drives inflation, each in metric and Palatini formalisms. We show that the ALP can be the dominant component of the dark matter in a wide range of its mass, m a ∈ [10−21 eV, PeV], depending on the inflationary scenario and the U(1) breaking scale. These results indicate that ALPs can be responsible for our dark matter abundance within a setup purely from non-perturbative gravitational effects.